Experiences for drought management plans in Cyprus - Tsiourtis N.X. (Drought management: scientific and technological innovations, 2008)
Cyprus is the third largest island of the Mediterranean Sea with an intense Mediterranean climate. The annual water availability is less than 500 m3/capita including sea water desalination and re-use of the treated domestic effluents. The natural water resources are almost fully developed with a master plan whose implementation lasted for 30 years starting in 1970. During the period 1970-2000 Cyprus suffered from 8 drought events lasting for 15 years out of 30, with rainfall below 85% of the average. A reduction of 15% of the rainfall brings an average reduction of the water resources of 30-40%. To accommodate the drought and minimize their adverse effects Cyprus was forced to modify its water policy by the introduction of seawater desalination, and accelerate the construction of new water projects and the recycling of the domestic effluents and to intensify the use of water demand methods and finally to develop and implement drought mitigation plans. Cyprus prepared and implemented drought mitigation plans successfully. This paper presents the procedure followed for the preparation of drought mitigation plans in Cyprus.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)